Beta-lactamases: clinical impact and epidemiology - Amyes, Sebastian (Henry Stewart Talks, 2009)
Beta-lactamases in Gram-negative bacteria, Beta-lactamase action, Emergence of the BIL-1 beta-lactamase, AmpC beta-lactamases, What are extended-spectrum beta-lactamases?, Active site of the TEM-1 beta-lactamase, Amino acid substitutions, European spread of CTX-M beta-lactamases, ESBL activity, Summary of OXA b-lactamases in Acinetobacter baumannii, Emergence of the NDM-1 beta-lactamase
Updated at 2015/11/30